Helping Her Heal‐Group: a pilot study to evaluate a group delivered educational intervention for male spouses of women with breast cancer. Issue 9 (15th March 2013) - Jones, Jennifer M.; Lewis, Frances Marcus; Griffith, Kristin; Cheng, Terry; Secord, Scott; Walton, Tara; Bernstein, Lori J.; Maheu, Christine; Catton, Pamela
Abstract: Background: Distress in husbands of women with early‐stage breast cancer may be equivalent to or even higher than their wives. Husbands often struggle to help and support their wives cope with the illness and its treatment. In response, we developed a five‐session group educational counselling intervention (Helping Her Heal‐Group (HHH‐G)) for husbands of women with early‐stage breast cancer. The primary aim of the current pilot study was to determine the acceptability and feasibility of HHH‐G and to obtain a preliminary estimate of its impact on participating men's skills, self‐confidence and self care. Secondary aims were to assess the impact of the intervention on both the participating spouses' and wives' ratings of marital quality and depressed mood. Methods: The study employed a one‐arm, pre–post‐intervention design whereby participating men ( n  = 54) and their wives ( n  = 54) independently completed measures at baseline (T0), immediately following the last session (T1) and 3 months after the last session (T2). Results: Overall, there was very high study retention (87%). On the basis of the questionnaire data, we found significant improvements in spouses' self‐efficacy ( p  < 0.001) and self‐reported skills including wife support ( p  = 0.003) and self‐care ( p  < 0.001). In addition, there was a significant improvement in wives' mood scores ( p  = 0.003). Post‐intervention interviews support acceptability and impact of the HHH‐G intervention, and provide support for the group format of the program. Conclusions: The feasibility and acceptability of HHH‐G was supported, and treatment outcomes suggest the potential benefits of the intervention. Phase III evaluation of HHH‐G program is warranted. Copyright © 2013 John Wiley & Sons, Ltd.